Money and banking: selected readings - Walters, A. A. (Harmondsworth : Penguin, 1973)
rpm 18/04/2018
Includes index.
Bibliography: p. 321-324.
This book of Readings discusses these crucial questions: What is the role of money? How does the supply of money affect real output, prices, interest rates, investment and savings in the economy? Does money matter?
Loans
Keywords: Money; Banks and banking